The impact of Differentiated Instruction Using VARK theory to Improve English Writing Proficiency of Tribal Learners in Kerala - Mini R G; Dr. S. Florence (Revista Electronica de Veterinaria, 2024)
This study examines the effectiveness of differentiated instruction using VARK (Visual, Auditory, Reading/Writing, Kinesthetic) model to improve English writing skills among tribal students in the Idukki district of Kerala, India. These  tribal students are experiencing challenges due to factors like poverty, linguistic barriers, and cultural isolation from traditional teaching methods like direct method. The primary objective of this study was to determine if an instructional approach tailored to individual learning styles could enhance the writing abilities of these marginalized students. A pre-test was conducted to 105 tribal students from grades 8 and 9 to check their writing skills, and they were grouped based on their VARK learning preferences after that. Over a ten-day intervention period, each group received instruction on key English grammar concepts through methods aligned with their specific learning style, such as visual charts, auditory discussions, written assignments, and kinesthetic role-playing. Following the intervention, a post-test were used to measure improvements in writing skills. Statistical analysis using a paired t-test showed a significant improvement in writing scores, with the mean score rising from 25.37 to 43.83. The findings suggest that a VARK-based differentiated approach is a powerful tool for enhancing academic performance and fostering a more inclusive and engaging learning environment for students in such contexts.